Agroecological assessment of pre‐emergence herbicides on sunflower crops in Krasnodar territory, Russia - V. A. Suvorova; A. P. Savva (Юг России: экология, развитие)
The aim was to undertake an Agroecological assessment of pre‐emergence herbicides on the crops of the Aris sunflower hybrid in Krasnodar Territory. The experiment was carried out at the Federal Research Centre of Biological Plant Protection in 2023 on sunflower crops (Aris hybrid), according to the guidelines for testing herbicides in agriculture. Widely used pre‐emergence herbicides were applied in the experiment. The biological and economic efficacy of herbicides was assessed by the number, weight and yield of sunflower seeds in comparison with the control. A comparative ecotoxicological assessment of the preparations was carried out based on the environmental load indicator.Application of the preparations: Frontiere Optima, CE (0.8 l/ha); Dual Gold CE (1.3 l/ha); Proponite, CE (2.0 l/ha), Gezadar, SC (2.0 l/ha), Begin Turbo, SC (1.5 l/ha); Acris, SE (2.0 l/ha); Versia, OD (3.0 l/ha) and Camelot, SE (3.0 l/ha) before sunflower germination provided 75...96 % herbicidal effect. No negative effect on the crop was observed and 149.1...155.5 % of the saved yield compared to the control was obtained. Herbicides: Frontiere Optima, CE, Dual Gold CE, Proponite, CE, Gezadar, SC are characterised by a lower environmental load compared to the preparations Begin Turbo, SC; Acris, SE; Versia, OD and Camelot, SE.When choosing herbicides for use on sunflower crops, it is necessary to take into account not only their biological effectiveness, but also their environmental load.